Risk assessment in the federal government : managing the process (National Academy Press, 1983)
The regulation of potentially hazardous substances has become a controversial issue. This volume evaluates efforts to develop and use risk assessment guidelines, reviews the experience of regulatory agencies with different administrative arrangements for risk assessment, and evaluates various proposals to modify procedures.